Revisiting the lectotypifications of Senecio plantaginifolius, S. setchuenensis and S. souliei (Asteraceae: Senecioneae) - Li, Cheng-Sheng; Chi, Xiao-Rui; Fei, Wen-Qun; Ren, Chen (Phytotaxa, 2022)
The problems about the original material and typifications of Senecio plantaginifolius (= Ligularia virgaurea), S. setchuenensis (≡ Synotis setchuenensis), and S. souliei (≡ Parasenecio souliei) have been revisited. The correct lectotype of S. souliei is the P00705033 sheet of Soulié s.n. designated by Koyama (Acta Phytotax. Geobot. 30: 75. 1979), and that of S. plantaginifolius should be Soulié s.n. (P02676722) designated by Hu (Quart. J. Taiwan Mus. 21: 137. 1968). For S. setchuenensis, it is better to only accept the P00705011 and P00705012 sheets of Soulié 198 as its original material, and the lectotype is P00705011 designated by Yu et al. (Pl. Diversity Resources 36: 593. 2014).